An asymmetric PCR-ELISA typing assay for Citrus tristeza virus (CTV) - Nolasco G.; Silva G.; Santos C. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
Typing of CTV based on coat protein (CP) gene has been approached in diverse ways. The basis for the assay focused on in this paper was presented some years ago and has been subject to several improvements since its appearance. Although the results obtained with this assay have been presented in diverse scientific meetings, theses and technical seminars, so far no paper has explained the rationale of the method or detailed the protocol. This is presented here as well as the discussion of recent developments regarding the set of probes, hybridisation procedure and software for interpreting the results.